Dampak Covid-19 Terhadap Tingkat Penjualan Pada Industri Barang Konsumsi Yang Terdaftar Di Bei - Hurriyaturrohman, Hurriyaturrohman; Indupurnahayu, Indupurnahayu; Agustin, Desi; Asvariwangi, Verni (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this study are to analyze the impact of Covid-19 on the level of sales in the consumer goods industry listed on the IDX in 2019-2020 and to analyze the level of company's sales before and after Covid-19 in the consumer goods industry listed on the IDX in 2019-2020. The research method used is quantitative research with purposive sampling technique. This study uses a sample of consumer goods industry companies in the food and beverage sub-sector that have published financial statements of 2019-2020 in the Indonesia Stock Exchange (IDX). This research uses simple linear regression method, Coefficient of Determination, Pearson Product Moment Correlation and Paired Sample T-Test with SPSS 25. The results of this study indicate that (a) Covid-19 affects the level of sales in the consumer goods industry listed on the IDX in 2019-2020 (b) There are differences in the level of sales before and after Covid-19 in the consumer goods industry listed on the IDX in 2019-2020. .